Evodiamine suppresses endometriosis development induced by early EBV exposure through inhibition of ERβ - Wang, Junling; Liang, Yuanqi; Liang, Xiaoru; Peng, Huijuan; Wang, Yongxia; Xu, Mingtao; Liang, Xuefang; Yao, Helen; Liu, Xiaohan; Zeng, Liqin; Yao, Paul; Xiang, Dongfang (Frontiers in Pharmacology, 2024)
Endometriosis (EMS) is characterized as a prevalent gynecological inflammatory disorder marked by the existence of endometrial tissues situated beyond the uterus. This condition leads to chronic pelvic pain and may contribute to infertility. In this investigation, we explored the potential mechanism underlying the development of endometriosis (EMS) triggered by transient exposure to either latent membrane protein 1 (LMP1) or Epstein-Barr virus (EBV) in a mouse model. Additionally, we examined the potential inhibitory effect of evodiamine (EDM) on EMS. We found that transient exposure to either EBV or LMP1 triggers persistent estrogen receptor β (ERβ) expression through epigenetic modifications in both endometrial stromal and epithelial cells, subsequently modulating EMS-related cell metabolism, encompassing gene expression, oxidative stress, mitochondrial function, cell proliferation and the release of pro-inflammatory cytokines. Furthermore, 4.0 µM of EDM can efficiently reverse this effect in in vitro cell culture studies. Additionally, 20 mg/kg body weight of EDM treatment can partly suppress EMS development in the in vivo EMS mouse model. In conclusion, transient EBV/LMP1 exposure triggers permanent ERβ expression, favoring later EMS development, EDM inhibits EMS development through ERβ suppression. This presents a novel mechanism for the development of EMS in adulthood stemming from early EBV exposure during childhood. Moreover, evodiamine stands out as a prospective candidate for treating EMS.